2019
DOI: 10.1016/j.rssm.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Early labour market trajectories of intermediate and second generation Turkish and Maghreb women in Belgium

Abstract: This study focuses on early labour market trajectories of Turkish and Maghreb origin women who graduated in Belgium (Flanders) between 2005 and 2016. In contrast to available literature that largely focuses on employment positions at one point, we assess whether there are ethnic differentials in entering a sustainable employment spell, operationalised as an employment spell of at least four consecutive quarters, leading to a gross monthly wage of at least 82% of the gross Belgian minimum wage and a work intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 34 publications
(54 reference statements)
0
30
0
2
Order By: Relevance
“…Having established these migrant-native differentials in childcare use, we then investigated whether the differential uptake of childcare arrangements between natives and migrants could be explained by differences in mothers' employment opportunities. Previous research has shown that compared to other European countries, Belgium has one of the largest employment gaps between native women and women of non-European origin (Corluy 2014;Noppe et al 2018;Rubin et al 2008), which extends into the second generation (Maes et al 2019;Noppe et al 2018). Because employment positions and the use of childcare are endogenous, we estimated mothers' employment opportunities rather than considering their observed employment positions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having established these migrant-native differentials in childcare use, we then investigated whether the differential uptake of childcare arrangements between natives and migrants could be explained by differences in mothers' employment opportunities. Previous research has shown that compared to other European countries, Belgium has one of the largest employment gaps between native women and women of non-European origin (Corluy 2014;Noppe et al 2018;Rubin et al 2008), which extends into the second generation (Maes et al 2019;Noppe et al 2018). Because employment positions and the use of childcare are endogenous, we estimated mothers' employment opportunities rather than considering their observed employment positions.…”
Section: Discussionmentioning
confidence: 99%
“…On average, second-generation migrants perform better on the labour market than first-generation immigrants. However, second-generation migrants, and particularly Turks and Moroccans, are often less educated than natives, and are already disadvantaged from the start of their professional careers (Baert, Heiland & Korenman 2016), which leads them to have lower employment rates and more unstable labour market positions than natives (Maes et al 2019). Additionally, women with a Turkish or Moroccan background tend to start family formation at younger ages than natives (Corijn & Lodewijckx 2009), which may prevent them from establishing a stable labour market position before they have children.…”
Section: Migration History In Belgiummentioning
confidence: 99%
See 2 more Smart Citations
“…Although the migrant-native employment gap is more pronounced among the first generation, studies have repeatedly shown that second-generation migrant womenand particularly women of non-European origin-have lower employment rates than natives and are overrepresented in part-time employment, temporary contracts and employment sectors with low wages and irregular working hours (FOD WASO and UNIA 2017;Heath et al 2008). These disadvantages compared to natives already emerge at the beginning of their professional career, particularly for Turkish or Moroccan origin women (Baert et al 2016;Maes et al 2019).…”
Section: The Belgian Contextmentioning
confidence: 99%